(untitled) (Colombia Medica, 2007)
Objectives: To assess the frequency and variability of eleven non-metric dental crown traits (winging, shovel-shape, double shovel shape, Carabelli trait, deflecting wrinkle, protostylid, groove pattern, cusp number, sixth and seventh cusps) in permanent (UI1/UI2/UM1/LM1) teeth, in order to understanding the ethnic influence and the biological distance of the sample in study. Materials and methods: In this descriptive and quantitative study, frequency and variability of twelve non-metric dental crown traits were analyzed, through the ASUDAS System, in dental casts from 84 African-Colombian children of both sexes (42 females and 42 males), in mixed-dentition from Puerto Tejada, Cauca (Colombia) inhabitants. Results: High frequencies of Carabelli trait in grade 5; and +5 y +6 groove patterns, suggests Western dental complex influence. High frequencies of protostylid (P point or foramen secum) and deflecting wrinkle that suggest Mongoloid influence from the miscegenation with regional indigenous groups were observed. Winging, shovel-shape, double shovel, cusp number and cusp 6 showed low frequencies. Bilateral symmetry and absence of sexual dimorphism were demonstrated (except winging, shovel-shape and protostylid).